Sosialisasi Pengintegrasian Nomor Induk Kependudukan (NIK) menjadi Nomor Pokok Wajib Pajak (NPWP) - Firdaus Firdaus; Achmad Fahruddin; Totok Adhi Prasetyo; Zanuar Anwari; Moch. Khoirul Faizin (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
Tax socialization is a very important and strategic activity because it is related to the delivery of information to the public or related parties regarding applicable tax regulations, policies, and obligations. Specifically related to the new regulations issued by the government, namely the integration of the National Identity Number (KTP) and Taxpayer Identification Number (NPWP), according to what is regulated in PMK Number 112/PMK.03/2022. This service activity is carried out at STAI Sangatta and is related to integrating KTP into NPWP. Implementation activities, starting from the process of activity planning, implementation, and evaluation in compiling and running the program, The method used in this service is the Participatory Action Research (PAR) method, where the author is directly involved in the socialization process. The result of this activity is to increase insight into the thinking and understanding of the STAI Sangatta academic community, especially related to the new regulation PMK Number 112/PMK.03/2022 and the procedures and processes for integrating NIK data into NPWP. The liveliness and enthusiasm of the participants showed a positive attitude. Therefore, activities like this need to be followed up with similar ones by inviting participants from the government, Micro, small, and Medium Enterprises, and the private sector.